Inorganic coating method for ink titanium dioxide with high dispersion, high gloss and high covering power
By employing a precisely designed three-step zirconium-aluminum coating method, the problems of insufficient gloss, whiteness, and hiding power of titanium dioxide products in inks have been solved, achieving improved high dispersibility and compatibility, and producing titanium dioxide products suitable for high-end inks.
Patent Information
- Application Number
- CN202511580983.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-31
- Publication Date
- 2026-01-27
AI Technical Summary
Existing methods are insufficient to guarantee the gloss, whiteness, and hiding power of titanium dioxide products in inks, while simultaneously improving their compatibility and dispersibility with the ink system.
A precisely designed three-step zirconium-aluminum cladding method is employed, which includes two-step deposition of zirconium oxide and aluminum oxide, performed under acidic and alkaline conditions respectively. Combined with organic treatment agents, the surface properties of titanium dioxide are optimized to improve gloss and compatibility.
A titanium dioxide product for inks with high dispersion, high gloss, and high hiding power was prepared, improving the application performance indicators of the product and making it suitable for the high-end ink field.
Smart Images

Figure CN121406159A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a method for inorganic coating of titanium dioxide ink with high dispersion, high gloss, and high hiding power, belonging to the field of titanium dioxide post-processing production. Background Technology
[0002] Titanium dioxide possesses highly stable physicochemical properties, exhibiting high refractive index, optimal opacity, and superior whiteness, while remaining non-toxic and harmless, making it the world's best white pigment. In ink applications, titanium dioxide products require high whiteness, excellent gloss, strong hiding power, and good compatibility with the system. In practical applications, untreated surface-modified titanium dioxide exhibits defects such as uneven particle size, high photochemical activity, and easy agglomeration, leading to uneven dispersion and low gloss in ink systems, severely limiting its applicability. Therefore, post-treatment modification of raw titanium dioxide can improve its dispersion stability in ink systems, thereby ensuring that key application performance indicators such as whiteness, hiding power, and gloss reach superior levels.
[0003] Chinese patent CN109321002A discloses a method for preparing a ternary coating of titanium dioxide (titanium dioxide) produced by the chloride process, consisting of silicon, zirconium, and aluminum. This method uses a mixture of zirconium, silicon, and aluminum for coating, but does not differentiate between specific coating processes, and it is only applicable to titanium dioxide produced by the chloride process.
[0004] Chinese patent CN108997790A discloses a method for producing high-gloss titanium dioxide. This method uses sodium hexametaphosphate as a dispersant, and zirconium oxychloride, aluminum sulfate, and sodium aluminate for zirconium and aluminum coating. However, this method only involves acidic aluminum coating and uses a single zirconium source.
[0005] Chinese patent CN104119702B discloses a zirconium-aluminum coating process for high-gloss, high-weather-resistant rutile titanium dioxide. This method employs an alkaline coating of zirconium and requires the use of soluble carbonates such as sodium carbonate and potassium carbonate.
[0006] Currently, gloss remains a critical bottleneck for titanium dioxide products, especially in demanding systems such as water-based, UV, or surface printing. The level of gloss directly determines whether a product can enter the high-end market. Furthermore, improving the compatibility of titanium dioxide with ink systems and increasing its dispersibility within ink systems are crucial for further optimizing key application performance indicators such as whiteness, hiding power, and gloss of titanium dioxide products. Summary of the Invention
[0007] The technical problem to be solved by the present invention is that existing methods cannot guarantee the key application performance indicators of gloss, whiteness and hiding power of titanium dioxide products, while improving compatibility with ink systems and improving dispersibility.
[0008] To achieve the above objectives, the technical solution of the present invention is as follows: A method for inorganically coating highly dispersed, high-gloss, and high-coverage titanium dioxide ink includes the following steps: a. Initial product selection; b. Initial pulping and dispersion; c. Inorganic zirconium oxide coating; d. Inorganic alumina coating, and the alumina film deposition is carried out in two steps, under acidic and alkaline conditions respectively; e. Drying, crushing, and addition of organic treatment agents.
[0009] In step a, the average particle size of the initial product is 200–230 nm, and the sphericity of the titanium dioxide particles is 1.2–1.4.
[0010] In step b, the pulping concentration is 300–600 g / L, and the added dispersant is at least one of sodium hexametaphosphate, sodium silicate, and isopropanolamine, with the total amount added relative to the mass ratio of TiO2 being 0.2%–0.5%.
[0011] In step c, the zirconium source of the coating agent is at least one of zirconium sulfate, zirconium chloride, and zirconium oxychloride, and its content is 0.2% to 1% of the mass of TiO2.
[0012] Furthermore, in step c, the pH value of the coating process is 9.5–10.5, and the temperature is controlled at 60–70 °C.
[0013] Furthermore, in step c, the coating process is either parallel or co-current, and the entire process is controlled within 0.5 to 2 hours; and the final curing time is controlled within 0.5 to 1 hour.
[0014] In step d, the aluminum source of the coating agent is at least one of aluminum sulfate and aluminum chloride. The total content of acidic and alkaline aluminum coating is 2% to 4% of the mass of TiO2, and the amount of aluminum coating under acidic or alkaline conditions is not less than 1% of the mass of TiO2.
[0015] Furthermore, in step d, alkaline aluminum coating requires a co-current process, with the initial pH value of the coating process being 9.5–10.5, and the coating agent being added in the correct order: first, the alkaline solution NaOH is added, followed by the coating agent. Acidic aluminum coating, on the other hand, requires a parallel flow process, with the pH value of the coating process being 3.5–4.5.
[0016] In step d, the coating process is carried out at a temperature of 60–70 °C; the curing time is 1.5–2.5 hours; and the pH value is 7.0–7.5 after the coating curing is completed.
[0017] Furthermore, in step e, the organic treatment agent is at least one of polyol, carboxylic acid, and organosilicon.
[0018] The beneficial effects of this invention are as follows: This method employs a precisely designed three-step zirconium-aluminum coating process to achieve precise modification of the surface properties of titanium dioxide. Zirconia can form a dense and continuous film on the surface of titanium dioxide particles, which can reduce microscopic roughness and passivate the surface states of titanium dioxide, reducing random scattering and improving the gloss of the product. The dense alumina film under acidic conditions further enhances the gloss and weather resistance of the product, while the loose and porous alumina film under alkaline conditions provides more surface hydroxyl groups, improving the compatibility of the product with the ink system. The titanium dioxide product for ink prepared using this method has the advantages of excellent whiteness, superior hiding power, and excellent gloss value, and has high practical value and promising prospects for improving the production quality of titanium dioxide products. Attached Figure Description
[0019] Figure 1 The graph shows a comparison of the whiteness of the titanium dioxide products prepared in Examples 1, 2, and 3 with that of existing products.
[0020] Figure 2 This is a comparison chart of the hiding power of titanium dioxide products prepared in Examples 1, 2 and 3 with existing products.
[0021] Figure 3 The image shows a comparison of the gloss of the titanium dioxide products prepared in Examples 1, 2, and 3 with existing products.
[0022] Figure 4 The images show physical photos of the titanium dioxide product prepared in Example 3 and existing products. Detailed Implementation
[0023] The present invention will be further described below with reference to the accompanying drawings and embodiments.
[0024] The present invention provides a method for inorganic coating of titanium dioxide ink with high dispersion, high gloss, and high hiding power, comprising the following steps: a. Initial product selection; b. Initial pulping and dispersion; c. Inorganic zirconium oxide coating; d. Inorganic alumina coating, and the alumina film deposition is carried out in two steps, under acidic and alkaline conditions respectively; e. Drying, crushing, and addition of organic treatment agents. Those skilled in the art will understand that this method, through precisely designed surface modification technology, achieves targeted control of the surface properties of titanium dioxide. On the one hand, it synergistically optimizes key application performance indicators such as gloss, whiteness, and hiding power; on the other hand, it enhances the compatibility of titanium dioxide with the ink system and improves dispersibility, ultimately obtaining a high-performance titanium dioxide product suitable for high-end ink applications. Furthermore, in step a of this method, to ensure the application performance indicators such as gloss and hiding power of the product, the average particle size and distribution of the initial product require certain conditions; therefore, the parameters of the initial product need to be controlled. Step b involves pulping and dispersing the initial product from step a. Through pulping and dispersion, the titanium dioxide initial product in water, under the action of mechanical stirring and dispersant, reduces the agglomeration of titanium dioxide particles and lowers the viscosity, forming a uniform and stable slurry, providing a good foundation for subsequent inorganic coating. Step c involves applying a zirconia coating to the titanium dioxide slurry obtained in step b, allowing zirconia to deposit on the surface of the titanium dioxide particles, forming the first coating layer. The zirconia film layer bonds well with the titanium dioxide surface, providing good gloss and hiding power. Step d involves coating the zirconium oxide-coated particles from step c with alumina, allowing for further alumina deposition on the sample surface. The alumina film deposition employs a two-step deposition method, performed under both acidic and alkaline conditions. The order of the acidic and alkaline deposition steps is not critical. Alumina deposited under acidic conditions provides a denser film with superior hiding power and whiteness, while alumina deposited under alkaline conditions offers better dispersibility. Step e involves washing, drying, crushing, and adding organic treatment agents to the sample obtained after the inorganic coating process in step d, yielding the final titanium dioxide product.
[0025] Preferably, in step a, the average particle size of the initial product is 200–230 nm, and the sphericity of the titanium dioxide particles is 1.2–1.4. Those skilled in the art will understand that, in order to ensure the product's gloss and hiding power, the average particle size and distribution of the initial product must meet certain conditions. Specifically, in step a, the preferred average particle size is 200–230 nm, and the sphericity of the titanium dioxide particles is 1.2–1.4.
[0026] Preferably, in step b, the pulping concentration is 300–600 g / L, and the added dispersant is at least one selected from sodium hexametaphosphate, sodium silicate, and isopropanolamine, with the total amount added relative to the mass ratio of TiO2 being 0.2%–0.5%. Those skilled in the art will understand that, in order to reduce the agglomeration of titanium dioxide particles, lower viscosity, and form a uniform and stable slurry, thus providing a good foundation for subsequent inorganic coating, the preferred pulping concentration is 300–600 g / L, and the added dispersant is at least one selected from sodium hexametaphosphate, sodium silicate, and isopropanolamine, with the total amount added relative to the mass ratio of TiO2 being 0.2%–0.5%. All dispersant amounts are expressed as a mass percentage of TiO2.
[0027] Preferably, in step c, the zirconium source of the coating agent is at least one of zirconium sulfate, zirconium chloride, and zirconium oxychloride, with a content of 0.2% to 1% by mass relative to TiO2. Those skilled in the art will understand that zirconium oxide can form a dense and continuous film on the surface of titanium dioxide particles, which can reduce microscopic roughness and passivate the surface states of titanium dioxide, reducing random scattering and improving the gloss of the product. To ensure coating quality and reduce costs, the zirconium source of the coating agent is preferably at least one of zirconium sulfate, zirconium chloride, and zirconium oxychloride, with a content of 0.2% to 1% by mass relative to TiO2. All coating agent contents are expressed as a percentage of TiO2 by mass.
[0028] Preferably, the pH value of the coating process in step c is 9.5–10.5, and the temperature is controlled at 60–70 °C. Those skilled in the art will understand that, in order to improve the coating effect, the pH value of the coating process is preferably 9.5–10.5, and the temperature is controlled at 60–70 °C.
[0029] Preferably, the coating method in step c adopts a co-current or parallel-current process, and the entire process is controlled within 0.5 to 2 hours; and the final curing time is controlled within 0.5 to 1 hour.
[0030] Preferably, in step d, the aluminum source of the coating agent is at least one of aluminum sulfate and aluminum chloride, and the total content of acidic and basic aluminum coating is 2% to 4% of the mass ratio of TiO2, and the amount of aluminum coating under both acidic and basic aluminum coating conditions is not less than 1% of the mass ratio of TiO2. The total content and amount of aluminum coating under both acidic and basic aluminum coating are expressed as a percentage of the mass of TiO2.
[0031] Preferably, in step d, the alkaline aluminum coating requires a co-current process, with an initial pH of 9.5–10.5, and the coating agent must be added in the order of NaOH solution first, followed by the coating agent. The acidic aluminum coating requires a co-current process, with a pH of 3.5–4.5 during the coating process. Those skilled in the art will understand that this method further specifies the order of the coating agents for alkaline and acidic coatings. Specifically, the alkaline aluminum coating requires a co-current process, with an initial pH of 9.5–10.5, and the coating agent must be added in the order of NaOH solution first, followed by the coating agent. The acidic aluminum coating requires a co-current process, with a pH of 3.5–4.5 during the coating process.
[0032] Preferably, the temperature during the coating process in step d is 60–70 °C; the curing time is 1.5–2.5 hours; and the pH value after coating curing is 7.0–7.5. Those skilled in the art will understand that, to ensure coating quality, it is actually preferred that the temperature during the inorganic alumina coating process be 60–70 °C; the curing time be 1.5–2.5 hours; and the pH value after coating curing be 7.0–7.5.
[0033] Preferably, the organic treatment agent in step e is at least one selected from polyols, carboxylic acids, and organosilicones. Those skilled in the art will understand that it is preferred that the organic treatment agent be at least one selected from polyols, carboxylic acids, and organosilicones, with polyols such as TMP being an example.
[0034] Example 1 The following method is used to produce a titanium dioxide product specifically for inks, which has high dispersibility, high gloss, and high hiding power. The specific operating steps are as follows: a. Initial Product Selection To ensure the product's gloss and hiding power, the initial particle size is 200 nm with a sphericity of 1.2.
[0035] b. Primary pulping and dispersion The initial product from step a was pulped and dispersed. The pulping concentration was 300 g / L, and the added dispersant was sodium silicate at a concentration of 0.2% (calculated as TiO2).
[0036] c. Inorganic zirconium oxide coating The titanium dioxide slurry obtained in step b is coated with zirconium oxide, causing zirconium dioxide to deposit on the surface of the titanium dioxide particles, forming the first coating layer. Specific parameters are as follows: zirconium sulfate is selected as the coating agent providing the zirconium source, with a content of 0.2%; the pH during the coating process is controlled at 9.7±0.2, and the temperature is controlled within the range of 60–64 ℃; the coating method adopts a co-flow process, with a coating time of 0.5 hours; the curing time is controlled at 0.5 hours. d. Inorganic alumina coating The alumina film deposition was performed using a two-step deposition method, sequentially under acidic and alkaline conditions. The specific process parameters were as follows: the coating agent providing the aluminum source was aluminum sulfate, with both acidic and alkaline coatings containing 1% aluminum; the acidic coating was performed first, followed by the alkaline coating; the acidic coating was a co-current process with a pH fluctuation range of 3.7 ± 0.2; the alkaline coating was a concurrent process, with an initial pH of 9.5, and NaOH solution was added first, followed by aluminum sulfate; the temperature during the coating process was controlled between 60 ± 2℃; the curing time was 1.5 hours; and the pH value after coating curing was 7.0.
[0037] e. Drying, crushing, and addition of organic processing agents After coating, the sample was sand-milled, and then washed, dried and crushed, and an organic treatment agent was added (in this example, the organic treatment agent was polyol TMP, and the amount added was 0.5%) to obtain the final titanium dioxide product, which was named Sample A.
[0038] Example 2 The following method is used to produce a titanium dioxide product specifically for inks, which has high dispersibility, high gloss, and high hiding power. The specific operating steps are as follows: a. Initial Product Selection To ensure the product's gloss and hiding power, the initial particle size is 220nm and the sphericity is 1.3.
[0039] b. Primary pulping and dispersion The initial product from step a was pulped and dispersed. The pulping concentration was 400 g / L, and the dispersant added was sodium hexametaphosphate at a concentration of 0.3% (calculated as TiO2).
[0040] c. Inorganic zirconium oxide coating The titanium dioxide slurry obtained in step b is coated with zirconium oxide, causing zirconium dioxide to deposit on the surface of the titanium dioxide particles, forming the first coating layer. Specific parameters are as follows: zirconium oxychloride is selected as the coating agent providing the zirconium source, with a content of 0.5%; the pH during the coating process is controlled at 10.0±0.2, and the temperature is controlled within the range of 65–68 ℃; the coating method adopts a co-flow process, and the coating time is 1 hour; the curing time is controlled at 1 hour. d. Inorganic alumina coating The alumina film deposition was performed using a two-step deposition method, sequentially under acidic and alkaline conditions. The specific process parameters were as follows: the coating agent providing the aluminum source was aluminum chloride; the aluminum content for acidic coating was 1%, and for alkaline coating, it was 2%, with acidic coating preceding alkaline coating; the acidic coating was a co-current process with a pH fluctuation range of 4.0 ± 0.2; the alkaline coating was a concurrent process, with an initial pH of 9.5, and NaOH solution was added first, followed by aluminum chloride; the temperature during the coating process was controlled between 67 ± 2℃; the curing time was 2 hours; and the pH value after curing was 7.3.
[0041] e. Drying, crushing, and addition of organic processing agents After coating, the sample was sand-milled, then washed, dried and crushed, and an organic treatment agent was added (in this example, the organic treatment agent was a mixture of polyol TMP and carboxylic acid, both added at 0.3%) to obtain the final titanium dioxide product, which was named Sample B.
[0042] Example 3 The following method is used to produce a titanium dioxide product specifically for inks, which has high dispersibility, high gloss, and high hiding power. The specific operating steps are as follows: a. Initial Product Selection To ensure the product's gloss and hiding power, the initial particle size is 230nm and the sphericity is 1.4.
[0043] b. Primary pulping and dispersion The initial product from step a was pulped and dispersed. The pulping concentration was 600 g / L, and the added dispersant was a mixture of sodium silicate and isopropanolamine, with addition amounts of 0.2% and 0.3% (calculated as TiO2), respectively.
[0044] c. Inorganic zirconium oxide coating The titanium dioxide slurry obtained in step b is coated with zirconium oxide, causing zirconium dioxide to deposit on the surface of the titanium dioxide particles, forming the first coating layer. Specific parameters are as follows: zirconium chloride is selected as the coating agent providing the zirconium source, with a content of 1.0%; the pH during the coating process is controlled at 10.3±0.2, and the temperature is controlled within the range of 67–70 ℃; the coating method is a co-current process, the coating time is 2 hours, and the curing time is controlled at 1 hour.
[0045] d. Inorganic alumina coating The alumina film deposition was performed using a two-step deposition method, sequentially under acidic and alkaline conditions. The specific process parameters were as follows: the coating agent providing the aluminum source was aluminum chloride; the aluminum content for acidic coating was 3%, and for alkaline coating, it was 1%, with alkaline coating performed first, followed by acidic coating; the alkaline coating was a co-current process, with an initial pH of 10.5, and NaOH solution was added first, followed by aluminum chloride; the acidic coating was a parallel-current process, with a pH fluctuation range of 4.3 ± 0.2; the temperature during the coating process was controlled between 68 ± 2℃; the curing time was 2.5 hours; and the pH value after coating curing was 7.5.
[0046] e. Drying, crushing, and addition of organic processing agents After coating, the sample was sand-milled, and then washed, dried and crushed, and organic treatment agent was added (in this example, the organic treatment agent was a compound of polyol TMP, carboxylic acid and silane coupling agent, with addition amounts of 0.1%, 0.1% and 0.3%, respectively) to obtain the final titanium dioxide product, which was named Sample C.
[0047] Domestic excellent ink product 1 and foreign excellent ink product 2 were selected as standard samples. Together with samples A, B, and C, the key performance indicators of the ink system—whiteness, hiding power, and gloss—were tested. Specific results are attached. Figure 1-3As shown, it is quite evident that the key application performance indicators of sample A, B, and C prepared using this method have reached a level comparable to that of excellent products both domestically and internationally. The excellent products mentioned here refer to domestic and international benchmark products tested under the same conditions and with the same ink system.
Claims
1. A method for inorganically coating highly dispersed, high-gloss, and high-coverage titanium dioxide ink, characterized in that... Includes the following steps: a. Initial product selection; b. Initial pulping and dispersion; c. Inorganic zirconium oxide coating; d. Inorganic alumina coating, and the alumina film deposition is carried out in two steps, under acidic and alkaline conditions respectively; e. Drying, crushing, and addition of organic treatment agents.
2. The method for inorganic coating of highly dispersed, high-gloss, and high-coverage titanium dioxide ink according to claim 1, characterized in that: In step a, the average particle size of the initial product is 200–230 nm, and the sphericity of the titanium dioxide particles is 1.2–1.
4.
3. The method for inorganic coating of titanium dioxide ink with high dispersion, high gloss, and high hiding power according to claim 1, characterized in that: In step b, the pulping concentration is 300–600 g / L, and the added dispersant is at least one of sodium hexametaphosphate, sodium silicate, and isopropanolamine, with the total amount added relative to the mass ratio of TiO2 being 0.2%–0.5%.
4. The method for inorganic coating of highly dispersed, high-gloss, and high-coverage titanium dioxide ink according to claim 1, characterized in that: In step c, the zirconium source of the coating agent is at least one of zirconium sulfate, zirconium chloride, and zirconium oxychloride, and its content is 0.2% to 1% of TiO2 by mass.
5. The method for inorganic coating of highly dispersed, high-gloss, and high-coverage titanium dioxide ink according to claim 4, characterized in that: In step c, the pH value of the coating process is 9.5–10.5, and the temperature is controlled at 60–70 °C.
6. The method for inorganic coating of highly dispersed, high-gloss, and high-coverage titanium dioxide ink according to claim 5, characterized in that: In step c, the coating process is either parallel or co-current, and the entire process is controlled within 0.5 to 2 hours; and the final curing time is controlled within 0.5 to 1 hour.
7. The method for inorganic coating of titanium dioxide ink with high dispersion, high gloss, and high hiding power according to claim 1, characterized in that: In step d, the aluminum source of the coating agent is at least one of aluminum sulfate and aluminum chloride. The total content of acidic and alkaline aluminum coating is 2% to 4% of the mass of TiO2, and the amount of aluminum coating under acidic or alkaline conditions is not less than 1% of the mass of TiO2.
8. The method for inorganic coating of titanium dioxide ink with high dispersion, high gloss, and high hiding power according to claim 7, characterized in that: In step d, alkaline aluminum coating requires a co-current process, with an initial pH of 9.5–10.5, and the coating agent must be added in the following order: first add the alkaline solution NaOH, then add the coating agent. Acidic aluminum coating requires a parallel flow process, with a pH of 3.5–4.
5.
9. The method for inorganic coating of titanium dioxide ink with high dispersion, high gloss, and high hiding power according to claim 1, characterized in that: The temperature during the coating process in step d is 60–70 °C; the curing time is 1.5–2.5 hours; and the pH value after coating curing is 7.0–7.
5.
10. The method for inorganic coating of titanium dioxide ink with high dispersion, high gloss, and high hiding power according to claim 9, characterized in that: In step e, the organic treatment agent is at least one of polyol, carboxylic acid, and organosilicon.
Citation Information
Patent Citations
A zirconium-aluminum coating process for high-gloss, high-weather-resistant rutile titanium dioxide
CN104119702B
Production method of high glossiness titanium dioxide
CN108997790A
Preparation method of chlorination-process titanium dioxide silicon-zirconium-aluminium ternary coating
CN109321002A